STAYCATION SEBAGAI WISATA ALTERNATIF MASA PANDEMI COVID-19 - Ni Luh Christine Prawitha Sari Suyasa; Putu Chris Susanto; Agus Satyananda M (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2022)
Restrictions on tourist mobility during the Covid-19 Pandemic led to a change in vacation trends, from Vacation to Staycation. The local community out of 255 respondents living in Badung Regency is familiar witho the word Staycation. 62.2% have done a staycation on both "one day trip" and "overnight" while 37.8% have never, but have the desire to do so in the near future. 56.4% are women and 30.2% age range 26- 30 years and 28.4% age range 40 - 50 years which is classified as productive age in work. 61.3% are private employees and 20.9% are entrepreneurs with an income range of Rp. 2,000,000 to Rp. 5,000,000 /month with a preference for staying in accommodation that has a swimming pool, a destination with a plantation atmosphere. The method of distributing an online survey is random aims to get characteristics and is supported by the results of interviews of each age. The data is further analyzed by bivariate methods to look at the relationship between characteristics and people's staycation desires which resulted in that age and income have a close relationship in deciding staycation wishes. The concept of staycation as alternative tourism has a positive impact on improving the economy of the local community through room occupancy rates in accommodation services as well as the level of visits to tourist destinations